Cabo Verde : Second Review Under the Policy Coordination Instrument and Request for Modification of Targets. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2020)
The Cabo Verdean economy is facing considerable challenges stemming from the impact of the COVID-19 pandemic. Prior to the health crisis, economic growth was robust, the fiscal and external positions were improving, reserves were at comfortable levels, and public debt was on a downward trajectory. The pandemic is threatening to erode these gains and has generated significant financing needs. The authorities have been implementing policy and healthcare measures to address the fallout of the pandemic and protect vulnerable groups while seeking to safeguard macroeconomic stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet